PRODUCTION OF CATFISH MEAT PROTEIN CONCENTRATE (Pangasius hypophthalmus) USING ETHANOL SOLVENT WITH DIFFERENT CONCENTRATIONS - MST Siagian, Roy; Ilza, Mirna; Sukmiwati, Mery (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research aims to determine the effect of ethanol solvent with different concentrations on the characteristics of catfish meat protein concentrates which include yield, proximate, and amino acids, to obtain optimal concentration. This research was conducted in 2 stages: first stage,the making of catfish meat flour, 2) making catfish meat protein concentrates using ethanol solvents with different concentrations (65% ethanol, 75% ethanol and 85% ethanol). The analysis showed that the use of ethanol solvent with different concentrations had a significant effect on the characteristics of protein concentrates. Ethanol solvent with a concentration of 85% was the best concentration in the production of protein concentrate with a yield, ash, water, protein, fat, and amino acid content was 80.42%, 19.44%, 6.35%, 68.37%, 0.55%, and50.25%, respectively. Keywords: Protein concentrate, catfish, ethanol